Not the Neo-Acadian orogeny: distinguishing Quaboagian deformation in New England from events in Atlantic Canada - Waldron, John W.F.; Barr, Sandra M.; White, Chris E.; van Rooyen, Deanne (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
The tectonic evolution of the northern Appalachian orogen is typically organized into orogenic episodes. The Taconian orogeny includes latest Cambrian to Late Ordovician arc-continent collision. Subsequent polarity reversal led to Silurian accretion of Ganderian terranes during Salinian orogenesis. The Acadian orogeny comprises Pridoli to Middle Devonian deformation attributed to accretion of West Avalonia to Laurentia. The term Neo-Acadian was coined by Robinson for Late Devonian to Mississippian shortening in New England, ca. 370–350 Ma, but the Indigenous-derived name Quaboagian was subsequently favoured for this episode.The “Neoacadian” later became associated with Meguma terrane docking, but clear convergent deformation in the Meguma terrane falls outside the original Neo-Acadian interval. Folding of strata in the Meguma terrane from ca. 409 Ma, concurrent with Acadian deformation, occurred in a different tectonic environment; emplacement of subduction-related plutons followed at mainly ca. 379–372 Ma. The ca. 370–350 Ma interval saw uplift of the Meguma terrane, local plutonism, and deposition of the Horton Group in a basin-and-range setting, whereas the crust beneath the Gulf of St. Lawrence thinned to less than half normal thickness during Maritimes basin development. These anorogenic transtensional basins were probably connected with Quaboagian shortening in New England via dextral strike-slip. Shortening and inversion resumed after ca. 330 Ma, associated with dextral transpression, docking the Meguma terrane close its present-day position.The misuse of "Neoacadian orogeny" leads to misconceptions about its timing of accretion and about ca. 370–350 Ma tectonics in Atlantic Canada, which involved extension not shortening. We recommend the term be abandoned in favour of Quaboagian and restricted to convergence in New England. Earlier deformation in the Meguma terrane may be attributed to the Kejimkujic orogeny.